1976
DOI: 10.1037/h0086491
|View full text |Cite
|
Sign up to set email alerts
|

Women's self-help groups as an alternative to therapy.

Abstract: In its form traditional therapy reflects our social institutions, parents, and relationships to authority. Women are trained to feel small and dependent and the form of regular therapy reinforces that, no matter what else (good) is going on. The self-help technique does everything to dispel the old form. It is especially important for women who are usually getting the worst end of our institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1982
1982
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Un centre de femmes a offert à sa clientèle une double formation aux rôles d'aidante et d'aidée. Après avoir acquis des habiletés comme l'écoute active et l'empathie, des petites équipes de trois à quatre femmes se sont rencontrées plusieurs fois pour les pratiquer (Glaser, 1976) en vue de devenir des personnes-ressources pour d'autres femmes.…”
Section: Leadershipunclassified
“…Un centre de femmes a offert à sa clientèle une double formation aux rôles d'aidante et d'aidée. Après avoir acquis des habiletés comme l'écoute active et l'empathie, des petites équipes de trois à quatre femmes se sont rencontrées plusieurs fois pour les pratiquer (Glaser, 1976) en vue de devenir des personnes-ressources pour d'autres femmes.…”
Section: Leadershipunclassified
“…First, Walker addresses the overall issue of the efficacy of women’s groups. Walker states that “several articles have been written espousing the benefits of all female therapy groups (Glaser, 1976; Klein, 1976; Meador et al., 1972; Wolman, 1976)” (p. 240). As these articles do propose in a theoretical format that women’s groups can be helpful, this initial statement is accurate.…”
Section: Critique Of Walker’s Conclusionmentioning
confidence: 99%
“…In view of the Indian culture and reticence to discuss personal difficulties, the use of self-help groups with Indian alcoholics was proposed by Kline and Robert, (1973). Other client populations currently participating in self-help groups are diverse and include the medically disabled (Guggenheim & O'Hara, 1976), alcoholics (Mueller, 1972), child abusers (Collins, 1978;Giaretto, 1976), males (Wong, 1978), females (Glaser, 1976), the obese (Wagonfeld & Wolowitz, 1968), parents of sudden infant death syndrome victims (Meier, 1973), families of schizophrenics (Craig, 1978), widows (Barrett, 1978), homosexuals (Stern, 1975), adolescents (Garbarino & Jacobson, 1978) and the chronically ill (Gussow & Tracy, 1976). In a review of the literature, Jaques and Patterson (1974) concluded that the concept of self-help is viable and necessary to the rehabilitation service systems.…”
Section: Benefitsmentioning
confidence: 99%